Integrating Direct Strategies in Teaching Tense Aspect System - Naura Naziva; Fitriyani Fitriyani; Masagus Firdaus (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Teaching the tense–aspect system has long posed challenges for English as a Foreign Language (EFL) learners due to its complex relationship between form, meaning, and use. Traditional grammar instruction in many EFL contexts often emphasizes rule memorization rather than meaningful application, resulting in learners’ limited ability to use tense forms accurately in communication. This study explores the integration of direct learning strategies—such as memory, cognitive, and compensation strategies—into the teaching of the tense–aspect system to enhance students’ grammatical competence and communicative accuracy. Using a mixed-method design, the research involved classroom implementation of direct strategies followed by tests, questionnaires, and observations. The findings indicate that learners who were taught using direct strategies showed significant improvement in recognizing and applying tense–aspect forms correctly. Moreover, students reported increased motivation, better retention, and greater confidence in using grammar communicatively. The results suggest that integrating direct strategies provides an effective framework for shifting grammar instruction from teacher-centered rule learning to student-centered strategy-based learning. It is recommended that EFL teachers combine direct strategies with communicative activities to promote both accuracy and fluency in language use.